D’un scandale l’autre: l’affaire Renaud Camus et la faillite de la critique intellectuelle - Ivan Jaffrin (Contextes)
In spring 2000, La Campagne de France, a volume of French writer Renaud Camus’ Diary gives rise to a scandale which provokes two contradicting petitions as well as an impressive number of articles in the French press. What first appeared to be a clear case of “racism and anti-Semitism” become an “affaire” involving a highly controversial collective process of definition. Making use of some of the works dealing with the notion of “scandale” and the social concept of “affaire” (Boltanski & Thévenot, 1991 ; Claverie, 1998) this article demonstrates that the “affaire Renaud Camus” is a “test” opposing two intellectual orders competing for the hegemony of interpretation of one and the same reality. The impossibility of solving the underlying dispute reflects a coercive principle in the dispute which this article seeks to identify by pointing out a few paralogisms. Finally, I argue that this dispute saw the demise of a certain form of intellectual critique and made way to a new state of the “social discourse” (Angenot, 1989) revolving around the notion of “multiculturalism”.